Development of the local taxation system as a basic financial resource of the municipal entities of the Republic of Adygea - L. V. Reunova (Новые технологии)
The article provides a detailed analysis of local taxation and the revenue base of local budgets of the Republic of Adygea. In particular, the role of local budget revenues in the structure of the consolidated budget of the Republic of Adygea is determined, as well as the structure of local budgets in terms of tax and non-tax revenues.Since local taxes make up an important part of revenues, the main attention is focused on the dynamics of revenues from land tax and property tax and factors affecting the volume of revenues from these taxes.Characteristic trends of local taxation in Adygea have been identified on the basis of the research and conclusions have been drawn on the sufficiency of financial resources for a complete fulfillment of the powers of local authorities and the need for additional gratuitous income. The directions of solving the financial problems of municipalities have been proposed.